STRATEGI KOMUNIKASI HUMAS DALAM MEMAKSIMALKAN SISTEM INFORMASI PEMERINTAH BERBASIS WEBSITE DI SETDAKAB KABUPATEN NAGAN RAYA - Ria Yunita; Reni Juliani (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2022)
In this study, the researcher examines the communication strategy carried out by the Public Relations of the Nagan Raya Regional Secretariat in maximizing website-based public services and what factors support and hinder in carrying out services with an online system. In this study, the researcher applied a qualitative research method with a descriptive approach and the determination of informants through purposive sampling with data collection techniques through direct observation to the field, interviews, and documentation. The results of the research conducted by researchers indicate that, the main strategy carried out by the Public Relations of the Nagan Raya Regional Secretariat in providing information to the public is to utilize information technology effectively, namely through the website of the local government of nagan raya kab.go.id which is managed by the Public Relations of the Regional Secretariat by forming an Information and Documentation Management Officer (PPID) SKPD, then Public Relations continue to maintain good relations with the public and the mass media, so that it becomes a strategy to support the Public Relations Secretariat in providing information to the public. In this case, the inhibiting factor, both in providing and accessing online-based services, is inadequate network disruption. While the supporting factors, the Nagan Raya district government agencies and other parties continue to provide support and encouragement to create excellent service using an online system. It is believed that the existence of online-based services can make it easier for the public to access various information within the government. We can see various regional information and we can access it quickly through this link.Keywords: Communication Strategy, Information System, Service.